ACE: apps to ace assignments / Alice Shanthi, Evelyn Sharminnie S Vasuthavan and Nurul Syafawani Halim - Shanthi, Alice; S Vasuthavan, Evelyn Sharminnie; Halim, Nurul Syafawani (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
When the world was first hit by the unprecedented Covid-19 pandemic, the education system was thrown into a disarray. UiTM was also not spared, however, as abruptly as teaching and learning came to a halt, most universities around the world made a swift change to adopt the rather choppy and unchartered waters of fully digitalized Online Direct Learning (ODL). Were the students prepared to learn on a fully digitalized platform? It is not easy to adopt or adapt to online learning in response to a sudden pandemic such as COVID-19 without encountering many problems and challenges. Students tace numerous challenges and problems due to the transfer to fully online learning (Al-Kumaim, et.al.,2021). Students were exposed to many new applications and programmers to learn in a fully digitalized platform (Jandric, 2020; Shanthi et.al., 2021). This added stress to the students as they had to familiarize themselves to the different tools used for different subjects (Shanthi, et.al., 2021). To further add to the stress of learning online was the process of completing some assignments which now had to be interactive with video and audio embedded in their presentations. There were evidence pointing out that students were falling behind in their academic performance because they lacked computer literacy skills (Jandric, 2020; Fernando et al, 2020). As an effort to help and guide students who lacked the computer literacy skill needed to complete their English coursework, a group of APB lecturers headed by Dr Alice Snanthi initiated a website called, ACE: Apps to Ace Assignments".